2009
DOI: 10.1002/eji.200839112
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic regulation of T effector to Treg ratios in an area of seasonal malaria transmission

Abstract: An important aspect of clinical immunity to malaria is the ability to down-regulate inflammatory responses, once parasitaemia is under control, in order to avoid immunemediated pathology. The role of classical (CD4 CD127lo/À FOXP3 1 ) Treg in this process, however, remains controversial. Thus, we have characterized the frequency, phenotype and function of Treg populations, over time, in healthy individuals in The Gambia. We observed that both the percentage and the absolute number of CD4lo/À T cells were highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
55
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 68 publications
11
55
0
Order By: Relevance
“…4) Although conventional memory T cells are regarded as long-lived cells [55,56], human Treg are thought to be short lived [42]; this has recently been linked to high levels of CD95 expression on human memory Treg [53]. We have observed transient expansion of FOXP3 1 Treg populations in a Gambian population exposed to seasonal malaria infection [38] suggesting that human Treg populations are highly dynamic. To determine whether activation-induced cell death by apoptosis might play a role in regulating Treg numbers, conventional T cells and FOXP3…”
Section: Foxp3mentioning
confidence: 87%
See 3 more Smart Citations
“…4) Although conventional memory T cells are regarded as long-lived cells [55,56], human Treg are thought to be short lived [42]; this has recently been linked to high levels of CD95 expression on human memory Treg [53]. We have observed transient expansion of FOXP3 1 Treg populations in a Gambian population exposed to seasonal malaria infection [38] suggesting that human Treg populations are highly dynamic. To determine whether activation-induced cell death by apoptosis might play a role in regulating Treg numbers, conventional T cells and FOXP3…”
Section: Foxp3mentioning
confidence: 87%
“…As for conventional T cells, it has been shown that the majority of CD4 T cells with regard to the expression of CCR and apoptotic molecules and suggest that CD25, rather than being a marker of Treg per se, is a marker of activated Treg. Given our interest in Treg function during malaria infection [38,[44][45][46][47], we further aimed to study these markers in relation to Treg activation status in vitro, using Plasmodium falciparum schizont extract (PfSE). Importantly, we show that -irrespective of the culture conditions -the phenotype of FOXP3 1 T cells is modified when they are kept in in vitro culture, affecting both expression of CCR and molecules involved in apoptosis, indicating a need for caution when comparing data from in vitro and ex vivo studies.…”
Section: Foxp3mentioning
confidence: 99%
See 2 more Smart Citations
“…FTY720 also has been shown to affect regulatory T cells (Tregs) by increasing the expression of IL-10 and CTLA-4 in vitro (55), promoting Treg activity in vivo (56) and more recently by modulating the reciprocal differentiation of inducible Tregs and Th1 cells (57). The role of Tregs in malaria infection remains controversial (58), and therefore the impact of S1P on this cell type during infection requires further investigation. Despite FTY720 mainly affecting T cells (15), an effect on B and NK cells cannot be excluded (59).…”
Section: Genetic Approaches Using Hs1plmentioning
confidence: 99%